2020
DOI: 10.1016/j.neuron.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Daily Oscillation of the Excitation-Inhibition Balance in Visual Cortical Circuits

Abstract: Highlights d The excitation/inhibition (E/I) ratio is dynamic across the 24h day d Fluctuations in the E/I ratio depend on sleep/wake history d E/I ratio changes are circuit specific, not uniform across all synapses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
156
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(176 citation statements)
references
References 64 publications
(82 reference statements)
18
156
2
Order By: Relevance
“…Moreover, E/I balance is not a static property of the cortex. It changes depending on the behavioral state (Waschke et al, 2019), task demands (Pfeffer et al, 2018;Waschke et al, 2019), performance (Sheehan et al, 2018) and depending on circadian rhythms (Bridi et al, 2020), which suggests that this property is under fine dynamic control. It has been proposed that cortical states and neural complexity could be regulated by subcortical cholinergic and noradrenergic activity (D'Andola et al, 2018); (Nghiem et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E/I balance is not a static property of the cortex. It changes depending on the behavioral state (Waschke et al, 2019), task demands (Pfeffer et al, 2018;Waschke et al, 2019), performance (Sheehan et al, 2018) and depending on circadian rhythms (Bridi et al, 2020), which suggests that this property is under fine dynamic control. It has been proposed that cortical states and neural complexity could be regulated by subcortical cholinergic and noradrenergic activity (D'Andola et al, 2018); (Nghiem et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The latter conclusion also has important implications for maintenance of excitatoryinhibitory (E-I) balance during SD. Recent data suggest that E-I balance normally varies over the course of the day, in a sleep-dependent manner (Bridi et al, 2020). Furthermore, prior evidence from both whole-tissue transcriptome profiling and immunohistochemistry has suggested that SD may differentially affect connections from excitatory to inhibitory neurons (and vice versa) in structures like the neocortex (Del Cid-Pellitero et al, 2017; Puentes-Mestril and Aton, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, within the neocortex, fast-spiking interneurons, or neurons with greater firing rates, appear to have differential firing rate changes across periods of sleep (Clawson et al, 2018;Vyazovskiy et al, 2009). Consistent with this idea, synaptic excitatory-inhibitory (E-I) balance was recently shown to vary in neocortex over the course of the day in a sleep-dependent manner (Bridi et al, 2020). Moreover, while most neocortical neurons fire at lower rates during slow wave sleep (SWS) vs. wake, some subclasses of neocortical neurons are selectively sleep-active (Gerashchenko et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…An alternative possibility is that sleep propensity may be enhanced if some of the strong wake-promoting areas are inhibited, consistent with the idea that sleep represents a default state of a neural network or the whole organism (Bandarabadi et al, 2020;Krueger et al, 2013). Therefore, even if accumulation of sleep need, in some form, occurs across many distributed brain networks (Bridi et al, 2019;Bruning et al, 2019;Honda et al, 2018;Lazarus et al, 2019;Muheim et al, 2019;Noya et al, 2019;Shi and Ueda, 2018;Tatsuki et al, 2016;Williams and Naidoo, 2020), it is likely that state switching is initiated from a relatively limited set of brain circuits, which have the capacity to integrate sleep-wake history related signals with other ecological and homeostatic demands. Whilst the biological substrate of global sleep homeostasis remains unclear, the question of which brain areas are involved in encoding the time spent awake or asleep seems tractable.…”
Section: Discussionmentioning
confidence: 66%